ANALISIS FAKTOR–FAKTOR YANG MEMENGARUHI WISATAWAN MELAKUKAN MEDICAL TOURISM DI MALAYSIA - Santoso, Indah Cahyani; Andajani, Erna; Megawati, Veny (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2020)
This study aims to analyze the factors that influence tourists to travel for medical tourism in Malaysia. The four main factors used were destination competitiveness, service quality, tourist attitudes, and costs, with 6 additional factors as supporting factors. This study used a quantitative approach. The data were analyzed using Confirmatory Factor Analysis run by SPSS and AMOS 22.0. The sampling technique used was non-probability sampling with the sample consisted of 100 respondents. Results showed that there were 44 elements adopted from the study. Based on the anti-image results, 5 factors were removed. According to the component rotation matrix table, 9 factors influence tourists to visit Malaysia for medical tourism. Then, these 9 factors labelled with the new names, i.e., internal and external factor, location attractiveness, ease of accommodation and services, tourist attraction and service quality, transportation and political condition, information and environment, medical service quality, medical tourism and language, and medical personnel. Keywords: cost, destination competitiveness , medical tourism , service quality, tourist attitude